Pattern Similarity Based Classification Using K-Nearest Neighbor and PSO Model for Cancer Prediction with Genetic Data - T, Sneka; K, Palanivel (International Journal of Computer Sciences and Engineering, 2019)
Data mining techniques can be used by Health organizations to predict different types of Cancer disease using individual Gene expression data. By using DNA (Deoxyribo Nucleic Acid) Microarray technology, thousands of genes can be articulated simultaneously. The objective of this research is to look closer on the classification issues in handling microarray data by introducing Semi-Supervised KNN (K-Nearest Neighbor) algorithm and Particle Swarm Optimization (PSO) as feature selection to cluster large amount of genetic microarray data. Also, using the predicted type of cancer, the severity level of cancer is diagnosed. Classifier performance is evaluated and it is shown in pie-chart and graph with improved accuracy. The proposed Semi-supervised learning method provides 10% improved accuracy in predicting cancer than the existing Supervised and unsupervised learning methods.